Analysis and validation of necroptosis-related diagnostic biomarkers associated with immune infiltration in bronchopulmonary dysplasia - Tu, Haixia; Fang, Changjiang; Gan, Ping; Gu, Yunyun; Peng, Nana; Jiang, Honghua; Hou, Weiwei; Shu, Guihua (Frontiers in Pediatrics, 2025)
BackgroundBronchopulmonary dysplasia (BPD) is the most common serious complication in very preterm infants. This study aims to identify necroptosis-related genes (NRGs) and analyze the relationship between necroptosis-related diagnostic markers and immune infiltration in BPD.MethodsWe obtained the dataset GSE32472 from the GEO database and analyzed the differentially expressed NRGs (DE-NRGs). We identified the biological functions and pathways of DE-NRGs. RF (random forest) and LASSO (least absolute shrinkage and selection operator) algorithms were applied to identify hub genes. We explored the immune landscape of BPD and controls by CIBERSORT. The correlations between hub genes and immune cells were evaluated using Spearman correlation analysis. ELISA was used to verify the diagnostic value of hub genes in patients with BPD in our hospital.Results27 DE-NRGs were screened. We found the primary biological functions and pathways of DE-NRGs, including necroptosis, and regulation of inflammatory response. Three hub genes (PELI1, PYGL, and STAT4) were identified and utilized to construct a diagnostic nomogram. The AUC value of the nomogram was greater than 0.7 in the validation dataset GSE188944. CIBERSORT showed that the proportions of 6 different immune cell types in the BPD group were higher or lower than the control group (P < 0.05). Correlation analysis showed that three hub genes may correlate with immune cells to varying degrees. Serum ELISA results of PELI1 and PYGL showed no significant difference between BPD and Controls (P > 0.05), the expression level of STAT4 was downregulated in BPD samples (P < 0.05), and the AUC value of the STAT4 was higher than 0.7.ConclusionThe necroptosis-related gene STAT4 can be a diagnostic marker of BPD patients. The necroptosis-related gene and immune infiltration may be related to the progression of BPD.